2012
DOI: 10.1371/journal.pone.0050791
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 Silencing in Mouse Colon Carcinoma Cells: The Effect on Tumoricidal Cytokines and Angiogenesis

Abstract: ADAM17 (a disintegrin and metalloprotease 17) is a major sheddase for numerous growth factors, cytokines, receptors, and cell adhesion molecules and is often overexpressed in malignant cells. It is generally accepted that ADAM17 promotes tumor development via activating growth factors from the EGF family, thus facilitating autocrine stimulation of tumor cell proliferation and migration. Here we show, using MC38CEA murine colon carcinoma model, that ADAM17 also regulates tumor angiogenesis and cytokine profile.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 55 publications
1
22
0
3
Order By: Relevance
“…In addition, ANXA9 was identified to be correlated with ADAM17, where MMP-9 is downregulated by mediation of AdAM17 (31). These results indicate that inhibition of ANXA9 expression levels in HcT116 cells may induce suppression of AdMA17 and MMP-9 expression levels, but increase the TIMP-1 expression level contributing to the weakness of tumor cells in invasion and migration (26,32). Epithelial-mesenchymal transition (EMT) contributes to the invasion and migration of cRc (33).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, ANXA9 was identified to be correlated with ADAM17, where MMP-9 is downregulated by mediation of AdAM17 (31). These results indicate that inhibition of ANXA9 expression levels in HcT116 cells may induce suppression of AdMA17 and MMP-9 expression levels, but increase the TIMP-1 expression level contributing to the weakness of tumor cells in invasion and migration (26,32). Epithelial-mesenchymal transition (EMT) contributes to the invasion and migration of cRc (33).…”
Section: Discussionmentioning
confidence: 95%
“…AdAM17 is a family members of disintegrin and metalloprotease, of which the upregulated expression in cRc participates in tumor progression (25). Furthermore, a previous study demonstrated that suppression of AdAM17 expression in the cRc cell, Mc38cEA results in inhibition of activity and migration (26). MMP-9, an important member of the MMP family, is significant in cRc progression (27,28), whereas TIMP-1 (an MMP-9 suppressor) inhibits MMP-9 and therefore decreases the ability of cancerous cells to invade and migrate (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…3c ). We hypothesize that ADAM17 could be an important target of the SP2043 peptide, as ADAM17 has been widely studied in angiogenesis and cancers 42 43 , and specifically in breast cancer 21 44 45 . Although CD58 and CD155 have not been directly implicated in angiogenesis and lymphangiogenesis, CD58 has been reported to promote self-renewal of tumor initiating cells 19 , and CD155 is known to induce tumor cell invasion and migration 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Das et al reported that ADAM17 silencing decreased the expression of vascular endothelial growth factor-A (VEGF-A) and MMP-9 in murine colon carcinoma cells (MC38CEA) and exhibited its antitumor immune response (41). Xiao et al found that the knockdown of ADAM17 can deactivate the EGFR-MEK-ERK signaling pathway, resulting in the downregulation of MMP-2 and MMP-9, therby reducing the invasive ability of prostate cancer cells (42).…”
Section: Discussionmentioning
confidence: 99%